Data Mining is becoming Extremely Powerful, but Dangerous - Kulathuramaiyer, Narayanan; Maurer, Hermann (Centre for Academic Information Services, UNIMAS, 2007)
Data Mining describes a technology that discovers non-trivial hidden patterns in a large collection of data. Although, this technology has a tremendous impact on our lives, the invaluable contribution of this invisible technology often goes unnoticed. This paper addresses the various forms of data mining shedding light on its expanding role in enriching our life. Emerging forms of data mining are able to perform multidimensional mining on a wide variety of heterogeneous data sources, to provide solutions to many problems. This paper highlights the advantages and disadvantages that arise from the ever-expanding scope of the data mining. Data Mining augments human intelligence by equipping us with the wealth of knowledge, empowering us to perform our daily task more effectively and efficiently. As the mining scope and capacity increases, users and organisations are now more willing (acceptable) to compromise privacy as a trade-off for gaining peace of mind and additional comforts. The huge data stores of the master miners allow them to gain deep insights about individual lifestyles, social and behavioural patterns and business and financial trends resulting in a disproportionate power distributions. Is it then possible to constrain the scope of mining while delivering the promise of better life?